NOD1/NOD2 and RIP2 Regulate Endoplasmic Reticulum Stress-Induced Inflammation during Chlamydia Infection - Oanh H. Pham (American Society for Microbiology, 2020)
ABSTRACT The inflammatory response to Chlamydia infection is likely to be multifactorial and involve a variety of ligand-dependent and -independent recognition pathways. We previously reported the presence of NOD1/NOD2-dependent endoplasmic reticulum (ER) stress-induced inflammation during Chlamydia muridarum infection in vitro, but the relevance of this finding to an in vivo context is unclear. Here, we examined the ER stress response to in vivo Chlamydia infection. The induction of interleukin 6 (IL-6) production after systemic Chlamydia infection correlated with expression of ER stress response genes. Furthermore, when tauroursodeoxycholate (TUDCA) was used to inhibit the ER stress response, an increased bacterial burden was detected, suggesting that ER stress-driven inflammation can contribute to systemic bacterial clearance. Mice lacking both NOD1 and NOD2 or RIP2 exhibited slightly higher systemic bacterial burdens after infection with Chlamydia. Overall, these data suggest a model where RIP2 and NOD1/NOD2 proteins link ER stress responses with the induction of Chlamydia-specific inflammatory responses. IMPORTANCE Understanding the initiation of the inflammatory response during Chlamydia infection is of public health importance given the impact of this disease on young women in the United States. Many young women are chronically infected with Chlamydia but are asymptomatic and therefore do not seek treatment, leaving them at risk of long-term reproductive harm due to inflammation in response to infection. Our manuscript explores the role of the endoplasmic reticulum stress response pathway initiated by an innate receptor in the development of this inflammation.